Influence of digital camera errors on the photogrammetric image processing - Sužiedelytė-Visockienė, Jūratė; Bručas, Domantas (Geodesy and Cartography, 2012)
The paper deals with the calibration of digital camera Canon EOS 350D, often used for the photogrammetric 3D digitalisation and measuring industrial and construction site objects. During the calibration data of the optical and electronic parameters, influencing the distortion of images, such as correction of the principal point, focal length of the objective, radial symmetrical and non-symmetrical distortions were obtained. The calibration was performed by means of the Tcc software implementing the polynomial of Chebichev and using a special test-field with the marks, the coordinates of which are precisely known. The main task of the research is to determine, how parameters of the camera calibration influence the processing of images, i.e. the creation of geometric model, the results of triangulation calculations and stereo-digitalisation. Two photogrammetric projects were created for this task. In the first the project non-corrected and in the second the corrected ones, considering the optical errors of the camera obtained during the calibration, images were used. The results of analysis of figures processing is shown in figures and tables. The conclusions are presented. Skaitmeninės fotokameros optikos klaidų įtaka atliekant fotogrametrinį nuotraukų apdorojimą Santrauka. Straipsnyje aprašytas skaitmeninės matuojamosios fotokameros Canon EOS 350D, dažnai naudojamos trimačiam arba dvimačiam fotogrametriniam objektų skaitmeninimui bei matavimams, kalibravimo procesas, kurio metu gauti objektyvo optikos sistemos parametrų duomenys – pagrindinio taško pataisa, objektyvo židinio nuotolis, radialinės simetrinės ir nesimetrinės distorsijos. Kalibravimas atliktas Tcc vokiška programa pagal Čebyševo polinomą, naudojant specialų erdvinį stendą su žinomomis pažymėtų taškų koordinatėmis. Tyrimo tikslas – nustatyti, kokios įtakos fotokameros kalibravimo parametrai turi fotonuotraukų apdorojimo, tai yra geometrinio modelio sudarymo, trianguliacijos skaičiavimų ir stereovektorizavimo rezultatams. Šiam tikslui sukurti du projektai. Pirmajame naudojamos fotonuotraukos, kuriose fotokameros objektyvo klaidos netaisytos, antrajame – pataisytos. Fotonuotraukų apdorojimo analizės rezultatai pateikti paveiksluose bei lentelėse. First published online: 03 Aug 2012